2022
DOI: 10.3389/fmicb.2022.953479
|View full text |Cite
|
Sign up to set email alerts
|

The cell wall and the response and tolerance to stresses of biotechnological relevance in yeasts

Abstract: In industrial settings and processes, yeasts may face multiple adverse environmental conditions. These include exposure to non-optimal temperatures or pH, osmotic stress, and deleterious concentrations of diverse inhibitory compounds. These toxic chemicals may result from the desired accumulation of added-value bio-products, yeast metabolism, or be present or derive from the pre-treatment of feedstocks, as in lignocellulosic biomass hydrolysates. Adaptation and tolerance to industrially relevant stress factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 315 publications
1
49
0
Order By: Relevance
“…Compared to the control, antioxidant dipeptides supplementation decreased the release of intracellular nucleic acid and protein, indicating that antioxidant dipeptides could decrease the cell wall damage caused by ethanol-oxidation cross-stress. Several studies have also demonstrated that the increase in CWI is essential for yeast survival under external stress. ,, In conclusion, the addition of antioxidant dipeptides under ethanol-oxidation cross-stress induced cell wall reshaping, improving cell wall rigidity and integrity, further protecting cells against multipressure.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Compared to the control, antioxidant dipeptides supplementation decreased the release of intracellular nucleic acid and protein, indicating that antioxidant dipeptides could decrease the cell wall damage caused by ethanol-oxidation cross-stress. Several studies have also demonstrated that the increase in CWI is essential for yeast survival under external stress. ,, In conclusion, the addition of antioxidant dipeptides under ethanol-oxidation cross-stress induced cell wall reshaping, improving cell wall rigidity and integrity, further protecting cells against multipressure.…”
Section: Resultsmentioning
confidence: 92%
“…Effects of antioxidant dipeptide supplementation on the yeast cell wall and membrane-related regulatory genes under ethanol-oxidation cross-stress. Schematic route (A): The external environment stress could trigger the response of the CWI pathway sensors, namely Wsc1–3, Mid2, and Mtl1 . These sensors interact with the guanine nucleotide exchange factor (GEF) Rom2 activating the small GTPase Rho1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition and thickness of the cell wall changes when cells encounter different environmental stresses and, the cell wall integrity (CWI) pathway is tightly regulated in response to different signaling pathways ( 23 , 24 ). The CWI pathway is activated through Slg1/Wsc1, Wsc2, Wsc3, Mid2, and Mtl1, which can couple with Rho1 and activate the MAPK cascade (Pkc, Bck1, Mkk1, and Slt2) ( 25 27 ). SsTOR -silenced strains are not sensitive to cell wall inhibitors and the mycelium is denser than the wild type.…”
Section: Discussionmentioning
confidence: 99%
“…Hrk1 was shown to mediate the phosphorylation levels of 40% of membrane-associated acetic acid-responsive proteins [96] . One important mechanism of tolerance to weak acids is the remodelling of the cell wall, and plasma membrane [103] , [104] , [105] , [106] . Increasing the synthesis of sphingolipids has been proposed to enhance the tolerance to acetic acid in S. cerevisiae based on the observed increase in sphingolipids in this yeast species upon acetic acid stress [107] .…”
Section: The Npr/hal Family Of Kinasesmentioning
confidence: 99%